Aripiprazole Lauroxil 2-Month Formulation With 1-Day Initiation for Acute Schizophrenia: ALPINE Exploratory Efficacy and Patient-Reported Outcomes. (April 2021) - Nasrallah, Henry; Walling, David; Weiden, Peter J.; Du, Yangchun; Yao, Baiyun; Yagoda, Sergey; Claxton, Amy
Abstract: Objective: The randomized, controlled, phase 3b ALPINE study evaluated efficacy and safety of a 2-month formulation of aripiprazole lauroxil (AL) initiated with a 1-day regimen during hospitalization for an acute exacerbation of schizophrenia; paliperidone palmitate (PP) was included as an active control. The primary efficacy outcome, within-group change from baseline in PANSS total score at 4 weeks, was previously reported. Here we report additional exploratory PANSS subscale endpoints and patient-reported outcomes (PROs). Methods: Adults aged 18–65 years were enrolled as inpatients and randomized to AL 1064 mg q8wk or PP 156 mg q4wk and discharged after 2 weeks of study treatment if clinically stable. Patients were followed as outpatients through week 25. Exploratory efficacy endpoints were PANSS subscale (Positive, Negative, and General) and Clinical Global Impression-Severity (CGI-S) scores. The Burden Assessment Scale was administered to patients' nonprofessional caregivers (family member or friend). Exploratory PROs (Quality of Life Enjoyment and Satisfaction Questionnaire Short Form [Q-LES-Q-SF] and Medication Satisfaction Questionnaire) were assessed during the outpatient period. Within-group changes in PANSS subscales and CGI-S scores from baseline through week 25 were analyzed for AL and PP using mixed models with repeated measures. PROs were summarized based on observed data. Results: In total, 200 patients were randomized (AL, n=99; PP, n=101); 99 (AL, n=56; PP, n=43) completed the 25-week study. PANSS Positive, Negative, and General subscale scores improved with AL treatment as measured by change from baseline to week 25 (least squares [LS] mean [95% CI]: Positive, −7.0 [−8.1, −6.0]; Negative, −3.7 [−4.7, −2.8]; General, −11.1 [−12.7, −9.5]), as did CGI-S scores (LS mean [95% CI] change at week 25: –1.2 [–1.4 –1.0]). Caregiver burden decreased over the treatment period, with the largest decline noted at week 9 for AL patients' caregivers (mean change from baseline at week 9: −8.4; week 25: −8.9). Over weeks 5, 9, and 17, 70.8%−74.7% of AL-treated patients were somewhat or very satisfied with treatment. Mean Q-LES-Q-SF total scores were stable. With PP, PANSS subscale and CGI-S scores improved from baseline to study end (LS mean [95% CI] changes at week 25: Positive, −7.1 [−8.2, −5.9]; Negative, −3.5 [−4.6, −2.5]; General, −10.4 [−12.1, −8.6]; CGI-S, −1.2 [−1.5, −1.0]). Mean caregiver burden decreased (week 9: −8.8; week 25: −9.2). Most PP patients were satisfied or very satisfied with treatment (64.7%−69.3% at weeks 5, 9, and 17), and mean Q-LES-Q-SF total scores were stable. Conclusion: In ALPINE, patients who initiated AL or PP in the hospital and continued treatment during outpatient care experienced improvement in schizophrenia symptoms and reported satisfaction with medication, decreased caregiver burden, and stable quality of life. Funding: Alkermes, Inc.